CULTURE, PRODUCT QUALITY AND PRICE EFFECT ON PURCHASE DECISIONS AND THE IMPLICATIONS ON CUSTOMER SATISFACTION (SURVEY AT GOLFER SHOE FACTORY IN CIBADUYUT, BANDUNG CITY) - Ony Y Djogo; Enung Susilawati (SAMPURASUN, 2020)
Efforts to support product business progress at the Cibaduyut shoe center currently need to be supported by technology, not only in production but also in marketing. Companies can take advantage of technological advancements by marketing products produced online. This system makes it easy for consumers to be used in choosing the desired product according to their needs. Anticipating competition among producers and achieving customer satisfaction, including the need to see good product quality and competitive prices, so that purchasing decisions occur. This study aims to determine the picture of product quality, price, purchasing decisions and customer satisfaction and the effect of the influence of product quality and price on purchasing decisions both simultaneously and partially. The research method used in this research is descriptive verification method with data collection techniques through questionnaires. The results showed that the quality of Golfer shoes was quite good on the model but was judged to be poor in terms of its durability. An assessment of the price is considered quite expensive, this can be due to tiered prices, consumer purchasing decisions on Golfer shoes products are considered less fast and customers are less satisfied with their products. Product quality has a positive and significant impact on purchasing decisions and their implications for customer satisfaction. Prices have a positive and significant effect on purchasing decisions and their implications for customer satisfaction. Simultaneously, product quality and price influence purchasing decisions. Purchasing decisions affect customer satisfaction. The direct influence of product quality on customer satisfaction and the direct effect of prices on customer satisfaction